The Influence of Culture on Client-Counselor Relationships in Cultural Diversity Adaptation Counseling - Deliati; Firman; Yarmis Sukur (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2024)
This study aims to analyze the influence of culture in the relationship between clients and counselors in the context of adaptation counseling. Using a qualitative approach, this study explores how cultural differences affect the counseling process and client adaptation in cultural diversity. The method used in this study is a literature review method. The results of the study indicate that understanding and recognizing cultural differences in counselor-client relationships can increase the effectiveness of counseling. This article also discusses practical implications for counseling practitioners in promoting more inclusive and culturally sensitive practices.